(untitled) (Plant Tissue Culture and Biotechnology, 2016)
Leaf explants were cultured to evaluate the effect of different auxins and cytokinins and its concentrations; MS salts on micropropagation of the promising biodiesel Jatropha curcas plant under Egyptian conditions. Results showed that shoot initiated on 0.5 mg/l BA + 0.25 mg/l IBA. Multiplication and elongation were found to be the best using 0.5 mg/l BA in combination with 0.05 mg/l IBA. The multiple shoots were cultured on MS or half strength of MS supplemented with different concentrations of IAA and IBA for rooting phase. Half strength of MS containing 1.0 mg/l IAA was the best for rooting of micropropagated shoots. The rooted plantlets were acclimated in sand : peat?moss mixture (1 : 1) successfully. Plant Tissue Cult. & Biotech. 26(1): 85-96, 2016 (June)